2017
DOI: 10.3389/fmars.2017.00095
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Marine Prokaryote Composition with Season and Depth Over an Arctic Polar Year

Abstract: As the global climate changes, the higher latitudes are seen to be warming significantly faster. It is likely that the Arctic biome will experience considerable shifts in ice melt season length, leading to changes in photoirradiance and in the freshwater inputs to the marine environment. The exchange of nutrients between Arctic surface and deep waters and their cycling throughout the water column is driven by seasonal change. The impacts, however, of the current global climate transition period on the biodiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
92
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 121 publications
(187 reference statements)
14
92
1
4
Order By: Relevance
“…Several cryptic taxonomic groups, such as Chloroflexi (SAR202), Marinimicrobia (SAR406) and various members of Deltaproteobacteria, were significantly enriched in EGC (Figure 5), and also consisted of a large number of unique OTUs in this region. These enriched taxonomic groups in the icecovered EGC were previously reported from surface waters in the western Svalbard region (WSC) during the Arctic winter (Wilson et al, 2017). Therefore, our results support and strengthen the hypothesis of Wilson et al (2017) that bacterial community dynamics in Fram Strait are to a large extent affected by seasonal variability (e.g., availability of light under changing sea ice conditions), rather than hydrographic differences between water masses.…”
Section: Functional and Regional Differences In Microbial Communitiessupporting
confidence: 90%
See 1 more Smart Citation
“…Several cryptic taxonomic groups, such as Chloroflexi (SAR202), Marinimicrobia (SAR406) and various members of Deltaproteobacteria, were significantly enriched in EGC (Figure 5), and also consisted of a large number of unique OTUs in this region. These enriched taxonomic groups in the icecovered EGC were previously reported from surface waters in the western Svalbard region (WSC) during the Arctic winter (Wilson et al, 2017). Therefore, our results support and strengthen the hypothesis of Wilson et al (2017) that bacterial community dynamics in Fram Strait are to a large extent affected by seasonal variability (e.g., availability of light under changing sea ice conditions), rather than hydrographic differences between water masses.…”
Section: Functional and Regional Differences In Microbial Communitiessupporting
confidence: 90%
“…However, monitoring the dynamics of heterotrophic microorganisms requires physical sampling. Wilson et al (2017) were the first to describe changes of bacterial community composition in the eastern Fram Strait throughout a polar year. In accordance with observations from other polar regions (Alonso-Sáez et al, 2008;Iversen and Seuthe, 2011;Ghiglione and Murray, 2012;Williams et al, 2012), their results showed that the extreme seasonality of polar marine ecosystems, with ice-covered dark winter conditions and extended irradiance in summer, leads to pronounced seasonal differences in heterotrophic bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental conditions in the Arctic are highly affected by seasonality. In accordance, seasonal changes in microbial community composition have been reported for different parts of the Arctic Oceans, i.e., the increase of Gammaproteobacteria, in association to phytoplankton bloom dynamics and increased concentrations of dissolved organic matter in the summer months (Alonso-Sáez et al, 2008;Buchan et al, 2014;El-Swais et al, 2015;Wilson et al, 2017). The fjord water used for our incubation experiments, taken in June, was indicative for a post-bloom situation, with high relative abundance of the phylum Proteobacteria (96.5%) and in particular the class Gammaproteobacteria, with up to 76.1% of all proteobacterial reads (Figure 4), similar to reports from other studies (Piquet et al, 2010;Zeng et al, 2013).…”
Section: In Situ Microbial Community Compositionsupporting
confidence: 84%
“…The increase of Gammaproteobacteria, in particular of taxa belonging to the order Alteromonadales including Glaciecola and Colwellia, has also been observed during marine phytoplankton spring blooms in lower latitudes (Tada et al, 2011;Teeling et al, 2012) and in the Arctic Ocean (Bano and Hollibaugh, 2002;Wilson et al, 2017). This suggests that they can rapidly proliferate in response to new carbon sources, including phytoplankton-derived organic carbon or tDOM as indicated in our study.…”
Section: Tdom Effects On the Coastal Microbial Food Websupporting
confidence: 78%
“…Amplification of complementary DNA (cDNA) and DNA was performed using a two‐step nested PCR approach with primers 519F and 806R targeting both the archaeal and the bacterial 16S rRNA gene V4 hypervariable region. Details regarding extraction, amplification and amplicon library preparation can be found in Wilson et al (). Libraries were sequenced at the Norwegian Sequencing Centre (Oslo, Norway) using their MiSeq platform (MiSeq Reagent Kit v2, Illumina, California, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%